Preventive Measures for Society – a KGB Psychological Impact Tool - Okuličiūtė, Lina (Genocidas ir rezistencija, 2011)
In Soviet times, Lithuanian Society suffered both spiritual and psychological terror. The KGB attempted by one means or another to rehabilitate people who did not reconcile with the Soviet regime. Preventive measures were applied against people whose political opinions were contrary to the Communist ideology, who became involved in public activities, the defence of human rights, and other activities that posed risk to the party nomenclature. At the request of the Communist Party of Lithuania, the prosecutor’s office strengthened measures to prevent public manifestations of anti-Soviet propaganda. Overall control of society was supplemented with the so-called preventive measures. They usually took the form of manipulative conversations, public condemnations “with the help of society”, administrative measures, measures involving agents and “trusted individuals”, at people’s workplaces, social organisations, and official reprimands. The radio, press, and lectures, as well as debates at workplaces where such “unreliable” people worked or studied were used. Personal (individual) preventive measures were one of the main forms of KGB activity used to prevent the hostile actions of citizens. The use of such measures was intended to change the political views of citizens by making them publicly renounce their beliefs, and forcing them to repent for their actions. It was not only individuals who experienced moral terror; their family members were also subject to preventive measures. The “guilty” people had to admit their guilt and promise that in the future no such actions would be repeated, and that they would pay for their transgressions with exemplary work and behaviour. Thus it can be said that the preventive measure was “an opportunity” for a Soviet citizen to correct himself, i. e. to be rehabilitated in the eyes of the Soviet power by condemning his “unacceptable” actions and promising not to repeat them again. After the preventive measures of the KGB, people lived under constant pressure and menace. These intimidating preventive conversations and public discussions of behaviour had a significant impact. They strongly affected people who had carried out anti-Soviet actions and temporarily or permanently frightened them away from these activities. People felt they did not belong to various areas of life. Only the most courageous people did not renounce their beliefs. In order to control people or exclude them from public life, the Soviet regime, with the aid of the KGB, applied preventive measures. They violated people’s human rights and demeaned their individuality.